Physiological Comparisons of Elite Male Visma Ski Classics and National Level Cross-Country Skiers During Uphill Treadmill Roller Skiing - Sagelv, Edvard H.; Engseth, Tina P.; Pedersen, Sigurd; Pettersen, Svein A.; Mathisen, Gunnar; Heitmann, Kim A.; Welde, Boye; Thomassen, Tor O.; Stöggl, Thomas L. (Frontiers in Physiology, 2018)
Longer distance cross-country ski races such as the Visma Ski Classics (VSC) (14-220 km) has recently gained attention in addition to the traditional Olympic distances (5-50 km) associated with cross-country (XC) skiing. These long-distance races are characterized by extensive use of the upper body while double poling (DP). While there is a substantial amount of research on Olympic distance XC skiing, the physiological capacities of VSC skiers has not yet been explored. We recruited seven elite male VSC skiers and seven well-trained national level male XC skiers to undergo three tests in the laboratory: 1) a one repetition maximum (1RM) strength test in a cable pulldown; 2) roller skiing tests on a treadmill (10.5% inclination) for determination of gross efficiency (GE) at submaximal speeds (8 and 10 km·h-1) in DP and diagonal stride (DS); 3) two ramp protocols to exhaustion (15% inclination, starting speed 7 km·h-1) in DP and DS for the assessment of peak and maximal oxygen uptake (V̇O2peak and V̇O2max), respectively. Compared with the national level XC skiers, the VSC skiers performed similar in the 1RM cable pulldown, displayed 12.2% higher GE in DP at 8 kmh-1 but did not display any difference at 10 kmh-1, and had lower blood lactate concentration and heart rate at both submaximal speeds. The VSC skiers had longer time to exhaustion compared with the national level XC skiers during the two ramp protocols in DS (18%) and in DP (29%). The V̇O2max was 10% higher in DS compared with DP, with no differences between groups. The V̇O2peak/ V̇O2max-ratio of 90% did not differ between the two groups. In conclusion, the main differences were lower cardiorespiratory and metabolic responses at submaximal speeds as well as longer time to exhaustion in VSC skiers compared to national level XC skiers. This suggest the main differences to be efficiency and oxygen extraction by small muscle mass between the VSC and national level XC skiers.